CZECH AMATEUR SATELLITE CONSTRUCTION - LAND OBSERVATION STATION - NOVOTNÝ, Jan; ZUKERSTEIN, Jaroslav (Trends in education, 2010)
This contribution presents research of space - especially construction of own small satellite, which will be send to a space orbit. This research is kept on Department of Applied Disciplines of Faculty of Production Technology and Management, J. E. Purkyně University. Students of study field Technical Education are participating on this unique space research project by means of their thesis.
Keywords: space research; land observation station; technical education; project.